Effects of Grazing Intensity on Features of Vegetation, Soil and Its Erosion in a Steppe Desert - Yang Yanan; Yang Zhenqi; Guo Jianying (Shuitu baochi tongbao)
[Objective] The effects of different grazing intensity on vegetation features, soil physical properties, and soil erosion in a steppe desert were determined in order to provide a scientific basis for soil erosion control, degradation and ecosystem restoration in this region. [Methods] The vegetation community, soil physical properties, and soil erosion processes of sample plots under four different grazing intensities (heavy, moderate, light, and no grazing) were studied in the Xilamuren desert steppe of the Inner Mongolia Autonomous Region by use of in-situ monitoring and simulation experiments. [Results] ① Average coverage, height, and aboveground biomass of the vegetation community decreased as grazing intensity increased, while species richness index, diversity index, and evenness index increased. ② Sand content of the soil increased with grazing intensity, and bulk density and infiltration of the surface soil (0—10 cm) were more affected by grazing. ③ Under the same rainfall intensity, soil erosion and sediment yield increased with increasing grazing intensity. Soil primary infiltration rate, Simpson dominance index, and sand content in the soil were the key factors affecting soil erosion features under different grazing intensity. [Conclusion] Grazing significantly influenced the desert steppe vegetation community characteristics and soil hydro-physical properties. Therefore, grazing intensity should be controlled to moderate intensity (i.e., two sheep units/hm2) or below. For steppe regions damaged by heavy grazing, soil erosion resistance can also be increased by soil improvement through the use of appropriate artificial reseeding and introduction of microorganisms.